Transformative changes in tree breeding for resilient forest restoration - Ray, Duncan; Berlin, Mats; Alia, Ricardo; Sanchez, Leopoldo; Hynynen, Jari; González-Martinez, Santiago; Bastien, Catherine (Frontiers in Forests and Global Change, 2022)
Deciding how to establish woodland in forest restoration is not straightforward as different outcomes may be obtained from different establishment approaches, each with cost implications and degree of success limitations attached. Planning restoration requires knowledge of site conditions, including how sites are likely to respond under climate change. For objectives of production and high timber quality it is likely that ground preparation will be used, and planting with forest reproductive material (FRM) of known traits, such as: high survival and growth in establishment, drought tolerance adequate for climate projections, good resistance to pests and pathogens. For objectives associated with biodiversity, carbon sequestration, water supply protection, soil protection, natural regeneration could be a less costly solution with a limited amount of assisted translocation of selected FRM to improve resilience. If objectives are for rewilding forest areas, a degree of natural colonisation perhaps with translocation of some FRM could be a solution. Ignoring site conditions and suitability of available sources of FRM for forest restoration is likely to provide unexpected results with a mix of open ground, scrub and scattered trees resulting from climate, herbivore, and browsing impacts. The recent B4EST EU Horizon 2020 project examined progress in novel rapid approaches for testing the quality of FRM from existing genetic trials. Here we review the work of B4EST to show the opportunities from transformative tree breeding in forest restoration schemes, including: new climate projection ensembles at high temporal and spatial resolution to develop norms of reaction and transfer models with genetic components; multi-environment genotype-phenotype associations and multi-locus genotype-environment associations in identifying drivers of local adaptation; techniques for genomic selection using single nucleotide polymorphism (SNP) arrays to derive functional traits from polygenic associations; work on seed orchard site and climate specific FRM and zones for deployment; and work on some of the forest ecosystem service benefits derived at a landscape scale. We conclude that tree-breeding will provide robust forest restoration for planting, and rewilding (assisted natural regeneration), and if not “ignoring” but instead assisting natural colonisation processes – tree breeding may improve long-term forest resilience under environmental change.